Life Stress and Coping Strategies of Chittagong University Students (Chittagong University Journal of Biological Sciences, 2024)
The purpose of the present study was to investigate life stress and coping strategies of Chittagong university students. The sample of the study consisted of 120 university students of whom 60. students were first year (30 male and 30 female) and remaining 60 was masters (30 male and 30 female). Each group again consisted of 15 science students and 15 arts students. They were selected purposively from Chittagong University and some residential areas of Chittagong. The ·Bengali version of the "Life Stress Questionnaire" (Fahim 2001 ) and "coping scale" (Huque 2004) were used for investigating the life stress and coping strategies ·respectively. ·The obtained data were analyzed by using t-test. Results reveal that the life stress of masters’ students were greater than first year students (t=2.87, df= l 18,· p